The application of Langgeh rights law in buying and selling of agricultural land in West Aceh Regency - Nila, Nila Trisna; Arfriani Maifizar; Ilka Sandela; Adella Yuana (Technium Social Sciences Journal, 2023)
The Government of Aceh is granted the option to investigate and execute several policies to protect and promote customary law, one of which is the Langgeh right, under Law Number 44 of 1999 respecting the Privileges of the Province of the Special Area of Aceh. The Langgeh right is a right that grows in the values of customary law in Aceh Province, but its application has decreased, so it is important to conduct a study to determine the implementation of Langgeh rights in buying and selling agricultural land in West Aceh Regency, as well as efforts to keep Langgeh rights alive in the people of West Aceh. The empirical legal research method was applied, with a descriptive approach. According to field research, not all people in West Aceh Regency use Langgeh rights when buying and selling agricultural land, particularly in Panton Reu Sub District, Woyla Sub District, and Pantee Ceureumin Sub District. This is due to the Aceh Traditional Council’s lack of role as an institution empowered to support the development of customs in the West Aceh Regency. The issues that are not optimal in the application of Langgeh Rights in people’s lives are a lack of budget and a lack of outreach and legal guidance. The Aceh Traditional Council can make efforts to ensure the availability of the budget included in the DIPA by the West Aceh Government in terms of fostering and supervising customs and traditions in West Aceh Regency, conducting outreach, training for traditional leaders, counselling to society, and publishing books on Langgeh rights.